Study on the migration performance of Cs(I) in the treatment of simulated radioactive wastewater by electrodialysis. (5th September 2022) - Xie, Yudong; Wang, Xiaowei; Men, Jinfeng; Qin, Feibo
Abstract: As a competitive radioactive wastewater treatment technology, electrodialysis (ED) has the advantages of low operating pressure and high cycles of concentration. In order to analyze the migration performance of radionuclides during the treatment of radioactive wastewater by ED, a radionuclide migration model was constructed based on the mass conservation law and Faraday's law with the typical radionuclide cesium as the research object. Experiments were carried out for the treatment of simulated radioactive wastewater in a small-scale ED system, and the average migration rate of radionuclides under different operating conditions was predicted by the model. The results showed that the experimental values of concentration and average migration rate of Cs(I) were significantly correlated with the calculated values of the model, in which the relative error of the average migration rate was 4.54%. The variation characteristics of Cs(I) concentration in diluted solution under different current and volume ratio conditions can be predicted by the model. The average variation rate of Cs(I) concentration decreases significantly with the increase of current and volume ratio. HIGHLIGHTS: A new model for Cs(I) migration by electrodialysis was constructed. Co(II) and Mn(II) did not affect the migration of Cs(I). The correlation coefficient r ≥ 0.97 and the relative error was 4.54% of the model. Optimal operating conditions: I = 0.6 Ilim, VR = 1:40. Energy consumption is 17.36% of the evaporation method. Graphical Abstract